A pilot investigation of the tricuspid valve annulus in newborns with hypoplastic left heart syndromeCentral MessagePerspective - Colton J. Ross, MS; Elizabeth J. Trimble, MD; Emily L. Johnson, PhD; Ryan Baumwart, DVM; Matthew A. Jolley, MD; Arshid Mir, MD; Harold M. Burkhart, MD; Chung-Hao Lee, PhD (JTCVS Open, 2022)
Objective: Hypoplastic left heart syndrome (HLHS) is a congenital disease characterized by an underdevelopment of the anatomical components inside the left heart. Approximately 30% of newborns with HLHS will develop tricuspid regurgitation, and it is currently unknown how the valve annulus mechanics and geometry are associated with regurgitation. Thus, we present an engineering mechanics-based analysis approach to quantify the mechanics and geometry of the HLHS-afflicted tricuspid valve (TV), using 4-dimensional echocardiograms. Methods: Infants born with HLHS (n = 8) and healthy newborns (n = 4) had their TVs imaged, and the data were imported to 3D Slicer. The annular curves were defined at 5 points in the cardiac cycle. The geometry and deformation (strain) of the TV annulus were calculated to elucidate the mechanics of this critical structure and to compare them between neonates with and without HLHS. Results: For the annular geometry, HLHS-afflicted newborns had significantly larger annular circumferences (20%-30%) and anteroposterior diameters (35%-45%) than the healthy patients. From a biomechanics' perspective, the HLHS patients had significantly smaller strains in the anterior segments (–0.1 ± 2.6%) during end-diastolic and end-isovolumetric relaxation (1.7 ± 3.0%) compared with the healthy counterparts (–13.3 ± 2.9% and 6.8 ± 0.9%, respectively). Conclusions: The image-based analysis presented in this study may provide novel insights into the geometric and mechanistic differences in the TV annulus between the healthy and HLHS newborns. Future longitudinal studies of the biomechanics of TV annulus and other subvalvular structures may inform our understanding of the initiation and development of tricuspid regurgitation and the design of optimal repairs in this challenging population.